Cannabidiol as a Treatment for Mood Disorders: A Systematic Review. (April 2020) - Pinto, Jairo Vinícius; Saraf, Gayatri; Frysch, Christian; Vigo, Daniel; Keramatian, Kamyar; Chakrabarty, Trisha; Lam, Raymond W.; Kauer-Sant'Anna, Márcia; Yatham, Lakshmi N.
Objective: To review the current evidence for efficacy of cannabidiol in the treatment of mood disorders. Methods: We systematically searched PubMed, Embase, Web of Science, PsychInfo, Scielo, ClinicalTrials.gov, and The Cochrane Central Register of Controlled Trials for studies published up to July 31, 2019. The inclusion criteria were clinical trials, observational studies, or case reports evaluating the effect of pure cannabidiol or cannabidiol mixed with other cannabinoids on mood symptoms related to either mood disorders or other health conditions. The review was reported in accordance with guidelines from Preferred Reporting Items for Systematic reviews and Meta-Analyses protocol. Results: Of the 924 records initially yielded by the search, 16 were included in the final sample. Among them, six were clinical studies that used cannabidiol to treat other health conditions but assessed mood symptoms as an additional outcome. Similarly, four tested cannabidiol blended with Δ-9-tetrahydrocannabinol in the treatment of general health conditions and assessed affective symptoms as secondary outcomes. Two were case reports testing cannabidiol. Four studies were observational studies that evaluated the cannabidiol use and its clinical correlates. However, there were no clinical trials investigating the efficacy of cannabidiol, specifically in mood disorders or assessing affective symptoms as the primary outcome. Although some articles point in the direction of benefits of cannabidiol to treat depressive symptoms, the methodology varied in several aspects and the level of evidence is not enough to support its indication as a treatment for mood disorders. Conclusions: There is a lack of evidence to recommend cannabidiol as a treatment for mood disorders. However, considering the preclinical and clinical evidence related to other diseases, cannabidiol might have a role as a treatment for mood disorders. Therefore, there is an urgent need for well-designed clinical trials investigating the efficacy of cannabidiol in mood disorders.